HOTEL GENERAL MANAGERS PERCEPTION OF FACTORS RELATED TO WOMEN CAREER PROGRESSION IN THE HOSPITALITY INDUSTRY AT THE COAST REGION OF KENYA. - NZIOKA, ALICE MUENI (My University, 2013)
This study was a descriptive survey and the research methods employed included both quantitative and qualitative. The study was conducted in the coastal region of Kenya. Records held by the Kenya Association of Hotel keepers and Caterers indicate that out of sixty six (66) hotel general managers for classified hotels at the coast region of Kenya only (3) 4% of women are in top management positions. The study sought to determine the factors that affect women career progression in the hospitality industry and the hotel‟s general managers‟ perceptions of such factors then determine whether the perception of the hotel general managers affects women career progression in the hospitality industry in Kenya. The literature outlined the theories that relate to women‟s career progression, discussed the role of women managersin the hospitality industry and reviewed previous studies on the factors that affect women‟s career progression. The population for this study comprised hotel general managers, departmental heads and supervisors from classified hotels at the coast and classified hotel owners operating hotel businesses at the coast region of Kenya. The study employed stratified random sampling technique and the respondents were purposively selected. The sample size for this study was thirty seven men and three women general managers, forty three female hotel departmental managers and supervisors and three chain hotel owners. To establish validity and reliability of the instruments a pre-testwas conducted and the coefficient of internal consistency-the split-half reliability method was used. The study used questionnaire; Focus Group Discussions and Personal Interview methods to collect data. Descriptive statistics, Content analysis, Pearson‟s correlation analysis and multiple regressions were used for data analysis. This study identified Job related characteristics, Socio-cultural and organizational factors,work and family conflicts and gender discrimination as the factors that affect women‟s career progression in the hospitality industry inthe coast region ofKenya. Job related characteristics had significant positive relationship with work and gender discriminationr = 0.991,p<0.01 while Socio-cultural and organizational factors had significant positive relationship with work and family conflict factors r = 0. 973,p<0.01). The perception model was expressed as Y = 16.81 + 1.87V1+ 5.69J2+ 1.15 F3+1.05W4. From the findings of this study it was concluded that although individually the perception of the hotel GM was influenced by their socio-economic and demographic factors their perception seemed to reflect the hospitality industry organizational culture and as such determine if the hospitality career was regarded as inclusive or exclusive of female employees. The study recommends that at the hotel level, corporate policy and senior executive commitment are key in formulating strategies to facilitate women‟s career progression to management and executive positions